Perlindungan Hukum Terhadap Konsumen Tabung Baja Elpiji Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Jo Peraturan Menteri Perindustrian Nomor 47/M-IND/PER/3/2012 - Harfan Jifari; Liya Sukma Muliya (Bandung Conference Series: Law Studies, 2023)
Abstract. National development aims to create a just and prosperous society based on law. Economic development in the era of globalization must be able to support the growth of the business world in such a way that it can produce a variety of goods and/or services that can improve people's welfare and at the same time obtain security certainty for goods and/or services obtained from trade without causing harm to consumers. The development of the national economy cannot be separated from the role of the government. One of the government's actions in its efforts to build the national economy for the welfare of the people is the conversion of the use of kerosene fuel to LPG (Liquified Petroleum Gas). At the beginning of the development of the use of LPG steel cylinders, the Government participated in supervising this program by increasing the guarantee of consumer security and safety. As mandated by Law Number. 8 of 1999 concerning consumer protection, the Government revised SNI 19-1452-2001 to become SNI 1452-2007. The revision is based on the aspirations of producers and consumers, as well as improving the safety aspects of LPG steel cylinders. Then SNI 1452-2007 was revised to become SNI 1452:2011. This study aims to find out the form of legal protection for consumers of LPG steel tubes in events that are detrimental to consumers according to the Consumer Protection Act Jo Regulation of the Minister of Industry Number 47/M-IND/PER/3/ 2012 and the form of Responsibility of LPG Business Actors in the Event of Losses to Consumers Due to Explosion of LPG Gas Cylinders Based on Law Number 8 of 1999 Concerning Consumer Protection Jo Regulation of the Minister of Industry No 47/M-IND/PER/2012. The method used in this study is this approach using a normative juridical approach. In this study, the authors used a descriptive analysis method, used data collection techniques through literature studies and by way of interviews, and analyzed using qualitative normative analysis methods.The results of this study for legal protection for consumers using LPG gas cylinders can be seen in the application of Article 4, Article 6 and Article 7UU No. 8 of 1999 concerning Consumer Protection. Provisions regarding the responsibilities of business actors are regulated in Article 19 of Law No. 8 of 1999 concerning consumer protection in general, and specifically in Article 9 of Permenperin No. 47/M-IND/PER/3/2012 concerning Enforcement of the Indonesian National Standard (SNI) for LPG Steel Tubes and Regulation of the Minister of Industry No. 48 of 2019 concerning Conformity Assessment Institutions in the Context of Enforcement and Supervision of the Indonesian National Standard (SNI) for LPG Steel Tubes. Abstrak. Pembangunan nasional bertujuan untuk mewujudkan masyarakat adil dan makmur berdasarkan hukum. Pembangunan perekonomian pada era globalisasi harus dapat mendukung tumbuhnya dunia usaha yang sedemikian rupa sehingga dapat menghasilkan beraneka barang dan/atau jasa yang dapat meningkatkan kesejahteraan masyarakat dan sekaligus mendapatkan kepastian keamanan atas barang dan/atau jasa yang diperoleh dari perdagangan tanpa mengakibatkan kerugian konsumen. Pembangunan perekonomian nasional tidak lepas dari peran pemerintah. Salah satu tindakan pemerintah dalam upayanya membangun perekonomian nasional demi kesejahteraan masyarakat adalah konversi pemakaian bahan bakar minyak tanah ke gas LPG (Liquified Petroleum Gas). Pada awal perkembangan penggunaan tabung baja LPG, Pemerintah turut serta mengawal program ini dengan meningkatkan jaminan keamanan dan keselamatan konsumen. Sebagaimana diamanatkan Undang-Undang Nomor. 8 Tahun 1999 tentang perlindungan konsumen, Pemerintah merevisi SNI 19-1452-2001 menjadi SNI 1452-2007. Revisi tersebut didasarkan pada aspirasi produsen dan konsumen, serta peningkatan aspek keamanan tabung baja LPG. Kemudian SNI 1452-2007 direvisi menjadi SNI 1452:2011 Penelitian ini bertujuan untuk mengetahui bentuk Perlindungan Hukum Terhadap Konsumen Tabung Baja LPG Pada Kejadian yang Merugikan Konsumen Menurut Undang-Undang Perlindungan Konsumen Jo Peraturan Menteri Perindustrian Nomor 47/M-IND/PER/3/2012 dan bentuk Tanggung Jawab Pelaku Usaha LPG Bila Terjadi Kerugian Terhadap Konsumen Akibat Ledakan Tabung Gas LPG Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Jo Peraturan Menteri Perindustrian No 47/M-IND/PER/2012. Metode yang digunakan dalam pada penelitian ini yaitu Metode pendekatan ini menggunakan pendekatan Yuridis Normatif, Dalam penelitian ini, penulis menggunakan metode deskriptif analisis, menggunakan teknik pengumpulan data melalui Studi kepustakaan dan dengan cara wawancara, dan dianalisis dengan mempergunakan metode analisis normatif kualitatif. Hasil penelitian ini bagi Perlindungan hukum terhadap konsumen pengguna tabung gas LPG dapat dilihat pada penerapan Pasal 4, Pasal 6 dan Pasal 7UU No. 8 Tahun 1999 tentang Perlindungan Konsumen.Ketentuan mengenai tanggungjawab Pelaku usaha diatur dalam Pasal 19 UU No 8 Tahun 1999 tentang perlindungan konsumen secara umum , dan secara khusus pada Pasal 9 Permenperin No. 47/M-IND/PER/3/2012 tentang Pemberlakuan Standar Nasional Indonesia (SNI) Tabung Baja LPGdan Peraturan Menteri Perindustrian No. 48 Tahun 2019 tentang Lembaga Penilaian Kesesuaian dalam Rangka Pemberlakuan dan Pengawasan Standar Nasional Indonesia (SNI) Tabung Baja LPG.